Obsessive trajectories in children and adolescents exposed to adverse events (coronavirus disease 2019: global crisis teaches) - Demaria, Francesco; Pontillo, Maria; Bertoncini, Ilaria; Vicari, Stefano (Frontiers in Psychology, 2025)
Adverse events (AEs), such as natural disasters, community violence and public health crises, impact global health and are associated with fear, anxiety and disorientation. AEs are related to both short-term and long-term mental health problems in children and adolescents. Particularly, research has shown a significantly higher prevalence of obsessive-compulsive disorder (OCD) in individuals with a history of trauma. This work aims to explore the obsessive-compulsive (OC) trajectories following an AE, considering the role played by individual vulnerability, anxiety and psychological consequences for children and adolescents. In this direction, Coronavirus Disease 2019 (COVID-19) pandemic has represented an ideal and unique AE of concomitant factors that can help to understand the obsessive trajectory. Our framework shows that intrusive flashbacks, following a traumatic experience, can turn into automatic intrusive thoughts that become persistent and emotionally intense, similar to obsessive reactions. Intrusive thoughts can evolve into obsessive patterns, leading to compulsive behaviors aimed at reducing discomfort. The nature of the traumatic event may influence the development of specific OC symptoms. Risk factors include individual vulnerability, such as developmental stage and emotional reactivity, which can exacerbate obsessive stress responses. Anxiety plays a key role, as increased stress can stimulate automatic intrusive thoughts and amplify OCD reactions, especially in younger individuals. Disruptions in daily life can further increase anxiety and maladaptive behaviors in children and adolescents, affecting psychological well-being. The psychological effects of AEs can continue well beyond the events themselves. It is necessary to monitor and support young people involved to prevent their development. Community and individual resources are essential to promote resilience following such events.